Ultimate avengers [videorecording (DVD)] - Hitch, Bryan (Lions Gate Home Entertainment, 2006)
The story of six independent heroes who, like it or not, must fight as one to save the world. Little do they know that their biggest threat will emerge from within their own ranks: the Incredible Hulk! First-ever animated movie from Marvel.